2000
DOI: 10.1038/labinvest.3780132
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Heterogeneity in the Human Prostate: Evidence for Epithelial Stem Cells

Abstract: Clonal analysis of human prostate epithelial cells was undertaken in order to identify stem cells. Two types of colony were distinguished, termed type I and type II. Type I colonies were relatively small and irregular and contained a loose mixture of differentiated and undifferentiated cells. In contrast, type II colonies were large, round, and homogeneous, consisting almost exclusively of small undifferentiated and dividing cells. The colony-forming efficiency was 5.8% +/- 1.8 for freshly isolated epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 32 publications
6
113
2
2
Order By: Relevance
“…GST-p), all localize preferentially in the basal cell compartment. That the adult human prostate contains stem cells (SCs) is also supported by the observation that a small number of cells within the prostate possess tremendous proliferative capacity and can form glandular-like structures in reconstituted systems (Hudson et al, 2000). Several populations of putative human prostate stem/progenitor cells have been reported, which include CK5 and CK18 double-positive (CK5 þ /CK18 þ ) intermediate cells (van Leenders et al, 2000;Wang et al, 2001;Tran et al, 2002;Garraway et al, 2003;Bhatia et al, 2005), the side population (SP) cells (Bhatt et al, 2003), and small populations of cells that preferentially express cell surface molecules CD44 (Liu et al, 1997), a2b1 (Collins et al, 2001), or CD133 (Richardson et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…GST-p), all localize preferentially in the basal cell compartment. That the adult human prostate contains stem cells (SCs) is also supported by the observation that a small number of cells within the prostate possess tremendous proliferative capacity and can form glandular-like structures in reconstituted systems (Hudson et al, 2000). Several populations of putative human prostate stem/progenitor cells have been reported, which include CK5 and CK18 double-positive (CK5 þ /CK18 þ ) intermediate cells (van Leenders et al, 2000;Wang et al, 2001;Tran et al, 2002;Garraway et al, 2003;Bhatia et al, 2005), the side population (SP) cells (Bhatt et al, 2003), and small populations of cells that preferentially express cell surface molecules CD44 (Liu et al, 1997), a2b1 (Collins et al, 2001), or CD133 (Richardson et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…This is partially based on the preferential survival of basal cells after castration and their ability to repopulate the luminal compartment upon androgen add-back (Isaacs 1987;Bonkhoff and Remberger 1996). In vitro studies have also shown that PSCA -basal cells can give rise to PSCA + intermediate cells coexpressing basal and luminal cytokeratins (Tran et al 2002) that can differentiate into luminal cells (Hudson et al 2000;Xin et al 2007). Other investigators have proposed a branched model of differentiation where the luminal and basal cells are in separate lineages, maintained by separate progenitor cells (Fig.…”
Section: The Prostate Gland and Adult Prostate Stem Cellsmentioning
confidence: 99%
“…2A), further indicating that this assay promotes differentiation. Hudson et al (2000) reported that two types of colonies can grow from primary human prostate cells: type I intermediate colonies and rare type II primitive basal cell colonies, suggesting that both stem and progenitor cells can thrive in this culture. These findings demonstrate that this assay could be Immunofluorescence stains show that colonies coexpress the luminal (CK8) and basal (CK5) cytokeratins (middle).…”
Section: In Vitro Colony-forming Unit Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…It is lagging behind most other cell types as usual. Evidence has been published for normal prostate epithelial stem or progenitor cells in the human [18][19][20] and mouse prostate. [21][22][23][24][25] Mouse data suggest that the stem cell compartment lies towards the base of the ducts near where they join the urethra.…”
mentioning
confidence: 99%